2020
DOI: 10.1002/ase.1987
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Short‐, Medium‐, and Long‐Term Success of an Embodied Learning Activity in the Study of Hand Anatomy for Clinical Application

Abstract: A student's own body provides an often disregarded site of knowledge production and corporeal wisdom. Learning via cognitive processes anchored in physical movement and body awareness, known as embodied learning, may aid students to visualize structures and understand their functions and clinical relevance. Working from an embodied learning perspective, the current article evaluates the use of an offline physical learning tool (Anatomical Glove Learning System; AGLS) for teaching hand anatomy for clinical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
1
5
1
Order By: Relevance
“…Triggering embodiment through movement execution enhanced functional anatomy learning at the end of a real learning semester. This result is in line with the scarce studies providing evidence of the positive impact of embodiment on anatomy learning using quantitative learning outcomes (Macken & Ginns, 2014;Dickson & Stephens, 2015;Cherdieu et al, 2017;Smyth et al, 2021;Yohannan et al, 2022). In previous studies, embodiment was triggered mainly through hand gestures.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Triggering embodiment through movement execution enhanced functional anatomy learning at the end of a real learning semester. This result is in line with the scarce studies providing evidence of the positive impact of embodiment on anatomy learning using quantitative learning outcomes (Macken & Ginns, 2014;Dickson & Stephens, 2015;Cherdieu et al, 2017;Smyth et al, 2021;Yohannan et al, 2022). In previous studies, embodiment was triggered mainly through hand gestures.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, this decrease of anatomical knowledge retention was not observed in the EXP group. This result is at odds with Smyth et al (2021) study who found that embodiment was associated with better short-term scores, but demonstrated no effect for long-term assessment. The absence of significant longterm learning gains in Smyth et al (2021) study may be linked to the nature of their assessments which consisted of clinical applications.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations